2019
DOI: 10.3390/toxins11120733
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol Induces Inflammatory Injury in IPEC-J2 Cells via NF-κB Signaling Pathway

Abstract: The aim of this study was to investigate the effects of deoxynivalenol (DON) exposure on the inflammatory injury nuclear factor kappa-B (NF-κB) pathway in intestinal epithelial cells (IPEC-J2 cells) of pig. The different concentrations of DON (0, 125, 250, 500, 1000, 2000 ng/mL) were added to the culture solution for treatment. The NF-κB pathway inhibitor pyrrolidine dithiocarbamate (PDTC) was used as a reference. The results showed that when the DON concentration increased, the cell density decreased and seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
(40 reference statements)
2
19
0
Order By: Relevance
“…At 2 µM of DON exposure, DON has been reported to up-regulate the expression of IPEC-J2 cell IL1-α, IL1-β, IL-6, IL-8, TNF-α, and MCP1 genes after 48 h of exposure, whereas, 0.5 µM exposure simulated expression of IL1-β, IL-6, and IL-8 genes, and down-regulated expression of IL1-α and MCP1 genes [200]. The up-regulatory effect of DON on IL-6, TNF-α, and IL1-β through the NF-κB pathway was also observed in IPEC-J2 cells after 24 h of DON exposure within the concentration range of 0.34 µM to 6.7 µM [162]. DON also reportedly induced a concentration-dependent increase in the secretion of IL-8 protein by Caco-2 cells through NF-κB after 48 h exposure [201], and [194] reported an increase in IL-8 protein secretion by Caco-2 cells after 12 h, which was associated with NF-κB, PKR, and p38 pathways.…”
Section: Effect Of Selected Mycotoxins On the Intestinal Immune Systemmentioning
confidence: 78%
“…At 2 µM of DON exposure, DON has been reported to up-regulate the expression of IPEC-J2 cell IL1-α, IL1-β, IL-6, IL-8, TNF-α, and MCP1 genes after 48 h of exposure, whereas, 0.5 µM exposure simulated expression of IL1-β, IL-6, and IL-8 genes, and down-regulated expression of IL1-α and MCP1 genes [200]. The up-regulatory effect of DON on IL-6, TNF-α, and IL1-β through the NF-κB pathway was also observed in IPEC-J2 cells after 24 h of DON exposure within the concentration range of 0.34 µM to 6.7 µM [162]. DON also reportedly induced a concentration-dependent increase in the secretion of IL-8 protein by Caco-2 cells through NF-κB after 48 h exposure [201], and [194] reported an increase in IL-8 protein secretion by Caco-2 cells after 12 h, which was associated with NF-κB, PKR, and p38 pathways.…”
Section: Effect Of Selected Mycotoxins On the Intestinal Immune Systemmentioning
confidence: 78%
“…Next, we further studied the mechanism of the above phenomenon that nontoxic-dose DON could aggravated LPS-induced intestinal inflammation and barrier dysfunction in IPEC-J2 cell monolayers. Many studies have reported that mycotoxins could regulate inflammatory cytokines through regulating nuclear factor-κB (NF-κB) signaling pathway ( Shao et al, 2019 ; Sugiyama et al, 2016 ; Wang et al, 2019b ; Zmora et al, 2017 ). In addition, NF-κB has been reported to regulate the tight junction barrier and NLRP3 inflammasome response to some extracellular stimuli ( Al-Sadi et al, 2010 ; Guo et al, 2019; Zmora et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2018) revealed that DON treatment induces toxicity and apoptotic cell death in piglet hippocampal nerve cells via the MAPK signaling pathway [40]. Further, Zhang et al (2020) reported that in IPEC-J2 cells, DON treatment induced the production of proin ammatory factors by activating p38 and ERK1/2 [18], while showed that treating IPEC-J2 cells with DON caused in ammatory injury via activation of the NF-κB signaling pathway [41]. With regard to the m 6 A-modi ed genes identi ed in this study, our RNA-seq and qPCR analyses indicated that CSF2 was differentially expressed the most signi cantly in DON-treated cells, and CSF2 was the most central protein in the constructed PPI network (Fig.…”
Section: Discussionmentioning
confidence: 99%